Intervensi Ergonomi Terhadap Kenyamanan Bekerja di Dapur Rumah Tinggal - Polniwati Salim (Bina Nusantara University, 2014)
Clothing, food, and shelter are basic human needs. In a common household, food is provided through the kitchen. However, a kitchen does not only serve that purpose it is also needed as a place for recreation and communication of the family. Because cooking is a daily routine and takes quite an amount of time, it is considered as a tedious and heavy job. And so, if someone does not cook/work properly in terms of the movements or follow the ergonomic requirements, it would easily make her/him down and make her/him less efficient. To overcome these problems, it is required to improve the environment by adjusting the height according to user’s anthropometry. With these steps, the family would hopefully change their work attitude. They would hopefully find cooking easier and less tiring; and make it more comfortable and ergonomic to cook in the kitchen.